Influence of Service Quality, Price Perception, and Product Availability on Customer Satisfaction at the AHASS Motor Center Gajahmada Semarang Workshop - Pinky Alviyani; Kurniani; Khairul Saleh (Politeknik Negeri Semarang, 2025)
This research is grounded in the decline of service visits that occurred at the workshop AHASS Motorcycle Center Gajahmada Semarang from March through April 2025. The study's main focus is to elucidate how customer satisfaction at the workshop AHASS Motorcycle Center Gajahmada Semarang is impacted by service quality, price perception, and product availability. This research employed a purposive sampling method, which is categorized as non-probability sampling, and involved 97 participants. The data were obtained using a questionnaire with a Likert Scale spanning from 1 to 6 and analyzed using SPSS version 26. The results of the T-test show that while product availability has a negative and insignificant impact on customer satisfaction. On the other hand, service quality and price perception have a positive and significant impact. The F-test results demonstrate that service quality, price perception, and product availability all have a significantly simultaneous impacted on customer satisfaction. This research is anticipated to offer a solution for determining the optimal marketing strategy in the face of competition in the Indonesia automotive industry at the workshop AHASS Motorcycle Center Gajahmada Semarang.